Groundnut production performance based on chemical fertilizer practices and its profitability conditions - Jahan, Mashrat; Sarker, Jaba Rani; Burman, Preetilata; Barman, Linnet Riya (International Journal of Agricultural Research, Innovation and Technology, 2023)
From the mid of the 19th-century chemical fertilizers were introduced into Bangladesh as an additional source of plant nutrients. After that the use of fertilizer in crop production increases. However, the extreme use of chemical fertilizers can create hazardous environmental degradation, which in turn can lower yields. So, the optimum level should maintain that can help in turn increase production. In this current study, 150 groundnut farmers in the research areas were taken based on their fertilizer application methods. It shows that the number of chemical fertilizer users constituted a major share of the total almost 44.67%. Among all the farmers, chemical fertilizer users incurred the highest return on investment by 1.48. Land area, cost of irrigation and chemical fertilizer affect the adoption of chemical fertilizer usage positively. The higher cost of production due to the application cost of inorganic fertilizer also increases the yield simultaneously. The study shows that farmers who avoid using fertilizer result in lower production compare to others. In that case, age and education were identified as factors that pushed the farmers towards chemical fertilizer and enjoying higher production. Int. J. Agril. Res. Innov. Tech. 12(2): 126-133, December 2022